Anti‐AGE activity of poplar‐type propolis: mechanism of action of main phenolic compounds. (18th July 2019) - Boisard, Séverine; Shahali, Youcef; Aumond, Marie‐Christine; Derbré, Séverine; Blanchard, Patricia; Dadar, Maryam; Le Ray, Anne‐Marie; Richomme, Pascal
Summary: This study aimed to compare the protective effect of two geographically distinct propolis against the formation of advanced glycation end products (AGEs). The polyphenol content of propolis extracts (EEPs) was analysed using HPLC‐DAD‐MS profiling and evaluated for their protective effects against pentosidine‐like AGEs. Dicarbonyl trapping capacities of major EEP compounds were determined using a methylglyoxal scavenging in vitro assay. Both propolis samples were characterised with high levels of pinobanksin derivatives exhibiting strong anti‐AGE properties. EEPs reduced AGE formation more effectively than well‐known natural AGE inhibitors such as quercetin or chlorogenic acid. Individual evaluations of the five major compounds in EEPs showed that flavonoids strongly inhibit the formation of AGEs by trapping dicarbonyl intermediates, whereas compounds such as caffeic acid derivatives only act as antioxidant agents. Propolis is thus a promising candidate for the prevention and control of AGE‐related chronic diseases. Abstract : Propolis collected from two distinct areas of Iran were evaluated for their effects on pentosidine‐like AGEs and free radicals. Major propolis phenolic components were screened for their ability to trap reactive dicarbonyl species such as methylglyoxal, an intermediate component in AGEs formation. HPLC‐DAD followed by MS analyses revealed that the majority of components showing strong anti‐AGEs properties used the anti‐dicarbonyl pathway through the formation of MGO adducts, while prenyl caffeate would rather use the antioxidant pathway.